2019
DOI: 10.1111/jdi.13042
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of carotid ultrasonography: Application for the management of patients with diabetes

Abstract: Carotid ultrasonography is a non‐invasive, simple and inexpensive modality to assess the severity of atherosclerosis. This article reviews related articles, summarizes the rationale for the application of carotid ultrasonography in clinical practice, and addresses the features and the limitations of carotid ultrasonography in cardiovascular risk prediction. Numerous large studies have confirmed that various carotid ultrasound measures, such as carotid intima‐media thickness, the presence or absence of carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 113 publications
0
25
0
5
Order By: Relevance
“…Variability in the measurement of CIMT makes it difficult to compare between studies or combine results from different studies [ 31 ]. Despite these limitations, many studies have demonstrated that CIMT is associated with the presence and severity of atherosclerosis and predicts cardiovascular events, as reviewed by Katakami et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variability in the measurement of CIMT makes it difficult to compare between studies or combine results from different studies [ 31 ]. Despite these limitations, many studies have demonstrated that CIMT is associated with the presence and severity of atherosclerosis and predicts cardiovascular events, as reviewed by Katakami et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the utility of cIMT measurements as predictors of CVD (reviewed by Katakami et al 23 ), although whether predictive power is independent of traditional risk factors is still unclear. A large part of the discrepancies in the literature is likely due to the different protocols used (which part of the carotid artery is measured, whether plaque is included or not, whether mean (IMTmean) or maximum (IMTmax) values are used) in the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A large part of the discrepancies in the literature is likely due to the different protocols used (which part of the carotid artery is measured, whether plaque is included or not, whether mean (IMTmean) or maximum (IMTmax) values are used) in the analyses. Indeed it has been reported that IMTmean and IMTmax differ in their predictive value 23 . Therefore the partial overlap in loci associated with IMTmean and IMTmax is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…However, apart from the qualitative assessment of the carotid plaque (i.e., present or absent), the quantitative assessment of plaque burden through the number of plaques, plaque thickness, or plaque area has rarely been assessed. This is relevant because each measure may reflect different atherosclerotic phenotypes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%